Design And Simulation Of Automated Material Handling System For Automotive Assembly Process - Mohd Saffar, Seha (2019)
Improvement of process parameters for effective and efficient material handling system in manufacturing industry has been studied extensively lately in view of observed increases in demand for high technology to increase production and profit. This thesis investigates an actual industrial problem relating to improvement in material supply system in production line and inventory system in a warehouse. A case study was selected as a method to collect data in actual industry situation. The study aims to assess the influence of automated material handling system in an automotive industry by proposing a new integrated system design by mean of numerical analysis on significant effect and influence on the system. The system performance of the proposed integrated design was measured and compared to the current system. The system design and analysis were performed using Quest software. The methodology consisted of six phases. Firstly, data were gathered from actual industry as a case study. These data served as guideline and offer input on design limitation of the proposed integrated system. Secondly, a design concept was proposed using standard principle of design consideration for manufacturing. A full factorial design with two levels of three factors was applied as the design of experiment to analyze the performance measure of the integrated system and the current system. This thesis concludes that the overall result shows that the bottleneck for transport system was reduced by about 87% and 85% reduced was observed for the storage system. The transport equipment was utilized 4 times greater than the current transport system. Due to increment in utilization, the production output increased four times from the current system. Overall result showed decrement in cycle time of 63% for model 4 compared to model 1. The constraint for this research work was the preparedness of manufacturing industry towards flexibilities and leans. For future improvement, the simulation clock can be set in order to establish appropriate environment and the transition distance of entities between movement and distance of each resource to the others are properly premeditated. Also, in-depth study on Quest software and additional study on Delmia v5 as alternative simulation tool can be considered for virtual 3D simulation with ergonomic human movement results and analysis.